Assessing the benefits of anaortic off-pump coronary artery bypass grafting - Ushioda, Ryohei; Hirofuji, Aina; Yoongtong, Dit; Sakboon, Boonsap; Cheewinmethasiri, Jaroen; Lokeskrawee, Thanin; Patumanond, Jayanton; Lawanaskol, Suppachai; Kamiya, Hiroyuki; Arayawudhikul, Nuttapon (Frontiers in Cardiovascular Medicine, 2024)
The procedure known as "aorta no-touch" (NT) or anaortic technique in off-pump coronary artery bypass grafting (OPCAB) is expected to reduce the perioperative risk of stroke. At our institution, we have performed the anaortic OPCAB with more frequency. The main purpose of the present study is to investigate whether anaortic OPCAB was really effective for perioperative stroke reduction.From April 2011 to July 2023, 2236 patients underwent isolated OPCAB in our single center. The patients were divided into the Anaortic group (NT, n=762) and the Aortic group (A, n=1474). The NT group was propensity score-matched (PSM) with the A group at a 1:1 ratio (NT n=640; A n=640), and matching was performed based on 26 covariates with preoperative clinical characteristics.In both unmatched and matched cohorts of the NT and A groups, there were no significant differences in new stroke rates between the groups (NT vs A; unmatched: 1.0% vs 1.2%, p=0.624; matched: 0.9% vs 1.3%, p=0.789). Univariable logistic analysis did not identify the anaortic technique as an independent factor negatively associated with new stroke events (OR=0.81, 95% CI=0. 35-1.86, p=0.624).The present study did not find the anaortic technique to reduce risk of perioperative stroke in OPCAB. To identify patient cohorts in which anaortic OPCAB is significantly beneficial, further large studies are needed.